Crystallization of a Polyamide 6/Montmorillonite Nanocomposite at Rapid Cooling. Issue 9 (6th December 2012) - Mileva, Daniela; Monami, Andrea; Cavallo, Dario; Alfonso, Giovanni C.; Portale, Giuseppe; Androsch, René
Abstract The crystallization behavior of a polyamide 6/organo‐modified montmorillonite (PA 6/OMMT) nanocomposite has been investigated by scanning chip calorimetry and wide‐angle X‐ray scattering, with emphasis placed on the evaluation of the effect of supercooling/cooling rate on the crystal/mesophase polymorphism of the PA 6 matrix. Presence of OMMT has negligible effect on the kinetics of formation of α‐crystals of PA 6 at low cooling rate while there is observed enhanced nucleation of γ‐mesophase on fast cooling. Furthermore, addition of OMMT leads to a distinct increase of the cooling rate required to completely vitrify the amorphous state. The performed experiments demonstrate that the nucleating effect of OMMT in PA 6/OMMT nanocomposites is of particular importance at cooling conditions relevant in polymer processing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>